MANAJEMEN STRATEGI PELAKSANAAN PROGRAM PADAT KARYA PANGAN DI KABUPATEN TIMOR TENGAH UTARA - Bekun, Stefanus (FIA UB, 2013)
Abstract : Management Strategy Implementation Programme for Integrated Food in North Central Timor. The implementation of Food Work Compact Program is the answer to the problems of poverty and powerlessness of rural community at North Timor Tengah District. It is true that the government attempts to do a strategy management for this Food Work Compact Program with innovative, creative and committed to work system. To understand this situation, qualitative descriptive research method is used. The objective of research is to describe and to analyze the strategy management of the implementation of Food Work Compact Program at North Timor Tengah District. The findings indicate that the strategy management of the implementation of Food Work Compact Program is lack of coordination, especially in the making of terraced planting field. Innovative and creative work system in Food Work Compact Program is hardly accepted by the community because it is considered as excessive workload and therefore the commitment of community to the implementation of Food Work Compact Program is relative less. Therefore, the local government must properly do the strategy management of the implementation of Food Work Compact Program by building more intensive coordination and developing competitive work system either with the implementing officer and the community as the field implementer of Food Work Compact Program. Keywords: Strategy Management, The Implementation of Food Work Compact program. Abstrak: Manajemen Strategi Pelaksanaan Program Padat Karya Pangan Di Kabupaten Timor Tengah Utara. Pelaksanaan program Padat Karya Pangan untuk dapat menjawab permasalahan kemiskinan dan ketidakberdayaan masyarakat desa di Kabupaten Timor Tengah Utara . Dengan Program Padat Karya Pangan pemerintah berusaha memenej strategi kegiatan tersebut dengan sistem kerja yang inovatif, kreatif dan berkomitmen . Untuk mengetahui kenyataan tersebut metode yang digunakan dalam penelitian ini yakni deskriptif kualitatif dengan tujuan penelitian yakni : mesdeskripsikan dan menganalisa manajemen strategi pelaksanaan Program Padat Karya Pangan di Kabupaten Timor Tengah Utara. Hasil temuan menunjukkan bahwa : dalam memenej strategi pelaksanaan Program Padat Karya Pangan terjadinya kurang koordinasi dalam pembuatan terasering, sistem kerja yang inovatif dan kreatif dalam Padat Karya Pangan sulit diterima masyarakat sebab dilihat sebagai beban kerja, sementara komitmen masyarakat kurang diwujudkan dalam pelaksanaan Program Padat karya pangan. Karena itu Pemerintah Daerah perlu memenej strategi pelaksanaan Program Padat Karya Pangan dengan membangun koordinasi lebih intensif dan membangun sistem kerja yang kompetitif baik oleh aparatur pelaksana maupun masyarakat yang melaksanakan program Padat Karya Pangan. Kata kuncinya : Manajemen strategi, pelaksanaan Padat Karya Pangan.